FAKTOR YANG BERHUBUNGAN DENGAN KEBERHASILAN PELAKSANAAN PROGRAM PROMOSI KESEHATAN RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS MAMAJANG KOTA MAKASSAR - Zaenal (Stikes Graha Edukasi Makassar, 2019)
Clean and healthy lifestyles in the household is an effort to empower members of the household in order to know, willing and able to practice clean and healthy living, as well as play an active role in the public health movement. This research aims to know the factors that relate to the implementation of the program of health promotion healthy households in the region of clinics Mamajang Makassar city. This research was conducted in the form of observational research with cross sectional research design, in this case include the factors predisposing i.e. employment, income, knowledge and attitude. The population in this research is the head of the family and every household in the workplace Clinics Mamajang Makassar city, sampling using the formula of Notoatmodjo (2012) with the number of samples 88 KK. Method of data collection is done by means of interviews and observations based on a questionnaire that has been compiled. Analysis data with three stages, namely analysis, univariate analysis bivariat and multivariate analysis. The results showed that there is no meaningful relationship between a factor of employment and earnings against the successful implementation of the program of health promotion healthy households in the region of clinics Mamajang Makassar city. While a knowledge attitude and factors are dominant factors related to the implementation of the program of health promotion healthy households. Therefore health services and clinics need to increase public awareness of living clean and healthy Behaviors (PHBS) so that the increase of knowledge and attitude as well as encourage people to behave in a clean and healthy life